Cernaan In Sacco Ransum Ternak Sapi yang Menggunakan Kulit Buah Jagung Amoniasi - Andayani, Jul (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2009)
An experiment was conducted to evaluate an improvement of corn peel with  ammoniation  in sacco  digestibility in  cow  ration.  Measured parameters in the current experiment were, in sacco degradation of   dry matter, organic matter and crude protein. This study was assigned into completely randomized design (CRD) with 5 treatments and 4 replications. The treatments were ; R0 = 70% Forage (100% grass + 0% Corn Peel) + 30 % Concentrate,  R1 = 70% Forage (75 % grass + 25% Corn Peel) + 30 % Concentrate, R2 = 70% Forage (50% grass + 50% Corn Peel) + 30 % Concentrate, R3 = 70%Forage (25% grass + 75% Corn Peel) + 30 % Concentrate, R4 = 70% Forage (0% grass + 100% Corn Peel) + 30 % Concentrate. Result of this study showed that the treatments were significantly (P<0,05) influence degradation of dry matter, organic matter and crude protein. The degradation after ammoniation significantly increased and were higher  than that  of  without  ammoniation.  It is concluded that ammoniation with urea of corn peel could  increase degradation and could be used asforage substitution in ration.